A comparison of immigrant and non-immigrant women’s decision making in abusive relationships - Amanor-Boadu, Yvonne (Kansas State University, 2009)
Male-to-female intimate partner violence (IPV) remains a significant social problem as research into its prevalence, incidence, severity, and resulting health consequences has documented. Just as we are beginning to understand some of the pieces of this problem in the United States, researchers and domestic violence advocates have called for expanding that understanding by exploring the range of risks involved in leaving a relationship with a violent man or in seeking help. In addition to the risk of personal physical harm, women in relationships with violent men may also consider the risk of harm to others, and the financial, social and legal risks to leaving (Hamby, 2008). Others have called for a better understanding of IPV through the examination of experiences of IPV within specific groups or subpopulations, such as with immigrant women (Menjívar & Salcido, 2002). This study uses Hamby’s (2008) holistic risk assessment, Choice and Lamke’s (1997) 2-part decision-making model, and a comparison between immigrant and non-immigrant women, to expand our understanding of the decisions women make about leaving their relationship and to seek help. With a sample of 1,307 women in the United Stated, similarities and differences between immigrant and non-immigrant women in the predictors to leaving and help seeking were determined through logistic regression analysis. Results indicate support for a holistic risk assessment such as Hamby’s (2008), and demonstrate significant differences between immigrant and non-immigrant women in their risks and barriers to leaving and help seeking. Nevertheless, examinations of the predictors to leaving and help seeking demonstrate many areas of similarity between immigrant and non-immigrant women in the ways they make decisions about leaving a relationship with a violent man or seeking help. Domestic violence advocates and therapists who work with women in relationships with violent men are encouraged to explore more fully the impact of the risks of harm to others, and the financial, social and legal risks to leaving or staying, and are further encouraged to expand their ideas of what women need once they leave, given the barriers that may make leaving more difficult for them.
Keywords: domestic violence; immigration; stay/leave; Sociology, Individual and Family Studies (0628)